Indian Financial Sector : Structure, Trends and Turns - Mohan, Rakesh (IMF Working Papers; Working Paper ;, 2017)
This paper traces the story of Indian financial sector over the period 1950-2015. In identifying the trends and turns of Indian financial sector, the paper adopts a three period classification viz., (a) the 1950s and 1960s, which exhibited some elements of instability associated with laissez faire but underdeveloped banking; (b) the 1970s and 1980s that experienced the process of financial development across the country under government auspices, accompanied by a degree of financial repression; and (c) the period since the 1990s till date, that has been characterized by gradual and calibrated financial deepening and liberalization. Focusing more the third period, the paper argues that as a consequence of successive reforms over the past 25 years, there has been significant progress in making interest and exchange rates largely market determined, though the exchange rate regime remains one of managed float, and some interest rates remain administered. Considerable competition has been introduced in the banking sector through new private sector banks, but public sector banks continue have a dominant share in the market. Contractual savings systems have been improved, but pension funds in India are still in their infancy. Similarly, despite the introduction of new private sector insurance companies coverage of insurance can expand much further, which would also provide greater depth to the financial markets. The extent of development along all the segments of the financial market has not been uniform. While the equity market is quite developed, activities in the private debt market are predominantly confined to private placement form and continue to be limited to the bluechip companies. Going forward, the future areas for development in the Indian financial sector would include further reduction of public ownership in banks and insurance companies, expansion of the contractual savings system through more rapid expansion of the insurance and pension systems, greater spread of mutual funds, and development of institutional investors. It is only then that both the equity and debt markets will display greater breadth as well as depth, along with greater domestic liquidity. At the same time, while reforming the financial sector, the Indian authorities had to constantly keep the issues of equity and efficiency in mind.